A Brief History of ‘Lone’ Atrial Fibrillation: From ‘A Peculiar Pulse Irregularity’ to a Modern Public Health Concern - S. Potpara, Tatjana; Y.H. Lip, Gregory (Current Pharmaceutical Design, 2015)
Ever since the original description of a ‘peculiar pulse irregularity’, atrial fibrillation (AF) has been studied extensively and has come a long journey from the recognition of its cardiac origins, to the modern concept of AF as a serious public health challenge with profound social and economic implications. This arrhythmia affects around 2% of adult population, and the most common underlying heart diseases accompanying AF in the modern era are hypertension, heart failure and coronary artery disease, as well as valvular heart diseases and numerous other cardiac as well as non-cardiac disorders which have been shown to predispose to AF. On occasions, AF occurs in young otherwise apparently healthy individuals (so called ‘lone AF’). For a long time, ‘lone’ AF has been believed to bear a favourable prognosis as compared to AF with underlying structural heart disease, but increasing evidence suggests that ‘lone’ AF patients represent a rather heterogeneous cohort, with highly variable individual risk profiles due to the presence of various subclinical cardiovascular risk factors or genetically determined subtle alterations at the cellular or molecular level. For these reasons, the existence of truly ‘lone’ AF has recently been questioned. In this review article, we present a brief history of the recognition of the public health burden of AF. We discuss some of the misconceptions and breakthroughs on modern knowledge on AF, including the rise (and fall) of the ‘lone’ AF concept.
Keywords: management